2016
DOI: 10.1177/0284185116641347
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of Acoustic Radiation Force Impulse Imaging with Virtual Touch IQ in breast ultrasound: diagnostic performance and reproducibility of a new technique

Abstract: Background Virtual Touch IQ (VTIQ) is a novel technique of quantitative sonoelastography that applies acoustic radiation force impulse (ARFI). Purpose To evaluate breast ARFI imaging with VTIQ in the clinical setting, with regard to reproducibility and diagnostic performance, and to specify cutoff limits for the differentiation of benign and malignant lesions. Material and Methods This retrospective study included 83 patients with 85 breast lesions (51 benign, 34 malignant) who received ARFI imaging with VTIQ.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 25 publications
(51 reference statements)
5
27
0
2
Order By: Relevance
“…In the history of elastography, many studies regard subcutaneous fat as a control with malignant or benign nodular. [14] In this study, the skin SWE of abdomen covered fatty layer (>20 mm) gained excellent agreement (0.81–0.96) in intra- and interobserver, confirmed that subcutaneous fat has little impact on skin SWE reproducibility. In physical structure, the thickness of subcutaneous fat above the anterior and lateral tibia shows a graded increasing trend from 1 to 6 mm (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…In the history of elastography, many studies regard subcutaneous fat as a control with malignant or benign nodular. [14] In this study, the skin SWE of abdomen covered fatty layer (>20 mm) gained excellent agreement (0.81–0.96) in intra- and interobserver, confirmed that subcutaneous fat has little impact on skin SWE reproducibility. In physical structure, the thickness of subcutaneous fat above the anterior and lateral tibia shows a graded increasing trend from 1 to 6 mm (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…[36] (n = 20) displayed LOA graphically from the mean of three repeated measurements using the MyotonPro device (Myoton, Tallinn, Estonia) in normal muscle belly and tendon. Several studies have calculated LOA in nonmusculoskeletal tissues using variable numbers of repeated measurements including liver [37], thyroid [38] and breast [38,39]-for example, Mulabecirovic et al [37] found no significant difference using five or ten readings when measuring liver stiffness. Using five measurements in the present study decreased the LOA from (−36%, +55%) to (−26%, +35%); however, we would recommend taking at least five measurements if feasible, to further reduce the LOA.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, studies have reported using the VTIQ method of SWE for the evaluation of breast lesions [2,[23][24][25][26][27][28][29]. Ianculescu et al [2] reported the sensitivity and specificity values of the VTIQ method as 80.4% and 73%, respectively, when the cutoff SWV was 3.31 m/s.…”
Section: Discussionmentioning
confidence: 99%